Glucagon-Like Peptide-1 as Predictor of Body Mass Index and Dentate Gyrus Neurogenesis: Neuroplasticity and the Metabolic Milieu. (23rd November 2014) - Coplan, Jeremy D.; Syed, Shariful; Perera, Tarique D.; Fulton, Sasha L.; Banerji, Mary Ann; Dwork, Andrew J.; Kral, John G.
Abstract : Glucagon-like peptide-1 (GLP-1) regulates carbohydrate metabolism and promotes neurogenesis. We reported an inverse correlation between adult body mass and neurogenesis in nonhuman primates. Here we examine relationships between physiological levels of the neurotrophic incretin, plasma GLP-1 (pGLP-1), and body mass index (BMI) in adolescence to adult neurogenesis and associations with a diabesity diathesis and infant stress. Morphometry, fasting pGLP-1, insulin resistance, and lipid profiles were measured in early adolescence in 10 stressed and 4 unstressed male bonnet macaques. As adults, dentate gyrus neurogenesis was assessed by doublecortin staining. High pGLP-1, low body weight, and low central adiposity, yet peripheral insulin resistance and high plasma lipids, during adolescence were associated with relatively high adult neurogenesis rates. High pGLP-1 also predicted low body weight with, paradoxically, insulin resistance and high plasma lipids. No rearing effects for neurogenesis rates were observed. We replicated an inverse relationship between BMI and neurogenesis. Adolescent pGLP-1 directly predicted adult neurogenesis. Two divergent processes relevant to human diabesity emerge—high BMI, low pGLP-1, and low neurogenesis and low BMI, high pGLP-1, high neurogenesis, insulin resistance, and lipid elevations. Diabesity markers putatively reflect high nutrient levels necessary for neurogenesis at the expense of peripheral tissues.